2019
DOI: 10.1111/apa.15061
|View full text |Cite
|
Sign up to set email alerts
|

Survey of paediatricians caring for children with life‐limiting conditions found that they were involved in advance care planning

Abstract: Aim Advance care planning (ACP) is a strategy to align future care and treatment with preferences of patients and families. This study assesses the experiences of ACP among paediatricians caring for children with life‐limiting conditions. Methods Paediatricians from five Dutch university hospitals and the national oncology centre completed a survey during May to September 2017, which investigated experiences with ACP in their most recent case of a deceased child and with ACP in general. Results A total of 207 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 31 publications
3
37
0
Order By: Relevance
“…Clinicians who take these factors into account when discussing the future with parents, might create more openness and deeper insight in parental preferences and underlying values. Ongoing research continues to report that key barriers for ACP as perceived by clinicians, are, in their perspective, related to parental factors [8]. Our study illustrates that those perceived barriers need to be approached from a different point of view.…”
Section: Discussionmentioning
confidence: 74%
“…Clinicians who take these factors into account when discussing the future with parents, might create more openness and deeper insight in parental preferences and underlying values. Ongoing research continues to report that key barriers for ACP as perceived by clinicians, are, in their perspective, related to parental factors [8]. Our study illustrates that those perceived barriers need to be approached from a different point of view.…”
Section: Discussionmentioning
confidence: 74%
“…6,7 Barriers to ACP in paediatrics have included the fear of causing emotional distress in families and difficulties identifying the right time to start. [6][7][8] A growing number of programmes that support the implementation of ACP have been reported in palliative care. 4 These interventions have mainly focused on adults and might need adjustment for use in paediatrics.…”
mentioning
confidence: 99%
“…Because of the huge lack of robust paediatric ACP research, I was eager to read the study by Fahner et al in this issue of Acta Paediatrica . The authors present the results of a survey of 207 paediatricians from six university hospitals in the Netherlands.…”
mentioning
confidence: 99%
“…The Fahner et al study showed that most topics related to ACP were not discussed with the children themselves. The most commonly discussed topic was their joy in living and even this was only discussed in 19% of the cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation